EFFECT OF CHEMICAL, BIO FERTILIZATION AND COMPOST TEA SPRAYING ON GROWTH AND PRODUCTIVITY OF ZANTEDESCHIA BULBS - Azza Ghazi; Eman Attia (Scientific Journal of Flowers and Ornamental Plants, 2016)
A pot experiment was carried out during two successive seasons of 2013/2014 and 2014/2015 in a split design to determine if compost tea spraying and Enterobacter cloacae KX034162  inoculation under phosphorus fertilization levels influence plant development, rhizome weight and chemical constituents of Zantedeschia  aethiopica plants. The study showed that generally E. cloacae KX034162 inoculation had a positive effect on growth, flowering and chemical constituents under the different phosphorus (p) fertilization levels. E. cloacae KX034162 inoculation under 50% P-rate of recommended dose combined with compost tea spraying resulted in a significant increase in plant height, number of leaves per clump, leaf area, shoot and rhizome fresh weight, rhizome dry weight, stalk length and diameter, inflorescence height and diameter, flowering spike fresh weight, N, P and K concentration in shoot, flowering period and flower date and increased activity of dehydrogenase in soil. While, total inflorescence clump-1 and vase life (days) were increased by inoculation with E. cloacae KX034162 under 75% P-rate of the recommended dose combined with compost tea spraying.